ARTERIAL HYPERTENSION AMONG INDIVIDUALS OF 25–64 YEARS OLD: PREVALENCE, AWARENESS, TREATMENT AND CONTROL. BY THE DATA FROM ECCD - S. A. Boytsov; Yu. A. Balanova; S. A. Shalnova; A. D. Deev; G. V. Artamonova; T. M. Gatagonova; D. V. Duplyakov; A. Yu. Efanov; Yu. V. Zhernakova; A. O. Konradi; R. A. Libis; A. V. Minakov; et al. (Кардиоваскулярная терапия и профилактика, 2014)
Aim. To study prevalence of arterial hypertension (AH), mean values of systolic and diastolic blood pressure (SBP, DBP), awareness of patients about their disease, medication consumption (MC) and efficacy of treatment in several regions of Russia.Material and methods. Representative selections were made in 9 regions of Russia: men (n=5563), women (n=9737) of 25–64 y.o., studied in 2012–2013 with the response 80%. Systematic stratified multilevel random selection was formed with localilty criteria (Kisch method). The Questionnaire on the presence of AH included: awareness of the patient about his disease, drug intake. BP measurement was performed on the right arm by automatic tonometer Omron in sitting position after 5 minutes resting. The mean value of two measurements was used. BP defined as SBP ≥140 mmHg, DBP ≥90 mmHg, or if the patient had taken antihypertensive therapy. Efficacy of treatment — the part of patients (in %) who reached target BP. Control group — part of patients (in %) with BP <140/90 mmHg. Statistic data calculation was done with computer-based statistic software — SAS with standardising by age stratification of Europe.Results. Mean SBP and DBP were 130,7±0,1 mmHg and 81,6±0,1 mmHg respectively. Prevalence of AH — 44%, higher in men (p<0,001). Prevalence of AH was higher in rural area citizens in men — 51,8% vs 47,5% (р<0,02) and in women — 42,9% vs 40,2% (р<0,05). Awareness was 67,5% in men, 78,9% in women. Medications were taken by 60,9% of women and 39,5% of men. Effectively treated were 53,5% of women and 41,4% of men. With the age the part of effectively treated decreases (p<0,0005). BP is under control only in 1/3 of women and 14,4% of men.Conclusion. The role of AH as one of the main modifiable risk factors of cardiovascular diseases is proved, however it is depressing that the percent of controlled AH is low. BP control is the main task of outpatient surveillance at every local outpatient department, where now less than a half of those affected are being observed.